Application of Language Politeness in Learning Activities at School - Kemal Alief; Nashruddin Nashruddin (JELITA, 2022)
Language politeness really needs to be shown and maintained in society because it is a characteristic of the human in all nations. Language politeness needs to be applied in all aspects of life. One of the important places to apply language politeness is in teaching and learning activities in schools. This research was conducted in a junior high school in Lahore city. Participants were 30 students of the VIII grade who were involved in learning activities with a teacher. The researchers found that in learning activities, all positive elements are very important to be applied. This is important because teaching and learning activities are the spearhead in instilling positive values ​​from teachers to students, students to teachers, and students to students. For this reason, teaching and learning activities or processes should be able to run with full politeness which is manifested through the language used. Language politeness in teaching and learning activities will have a positive impact on students’ views of teachers, teachers to students, and students to students.